2016
DOI: 10.3390/molecules21070838
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Deoxynivalenol-3-β-d-[13C6]-glucoside and Application in Stable Isotope Dilution Assays

Abstract: Abstract:Modified mycotoxins have been gaining importance in recent years and present a certain challenge in LC-MS/MS analysis. Due to the previous lack of a labeled isotopologue of the modified mycotoxin deoxynivalenol-3-glucoside, in our study we synthesized the first 13 C-labeled internal standard. Therefore, we used the Königs-Knorr method to synthesize deoxynivalenol-3-β-D-[ 13 C 6 ]-glucoside originated from unlabeled deoxynivalenol and [ 13 C 6 ]-labeled glucose. Using the synthesized isotopically-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…A possible approach to cope with the matrix effect is represented by stable isotope dilution assay (SIDA) [26]. Multi-mycotoxins methods applying this technique have been developed [27,28], also thanks to in-house synthesis of labeled isotopologue mycotoxin standards, including isotopologues of modified forms (i.e., DON3Glc, 3Ac-DON, 15Ac-DON) [29]. Authenticity and method performance have been demonstrated by analyzing naturally contaminated samples, such as malt, beer and maize [30].…”
Section: From Targeted Lc-ms/ms Determination To Untargeted Hr-ms mentioning
confidence: 99%
“…A possible approach to cope with the matrix effect is represented by stable isotope dilution assay (SIDA) [26]. Multi-mycotoxins methods applying this technique have been developed [27,28], also thanks to in-house synthesis of labeled isotopologue mycotoxin standards, including isotopologues of modified forms (i.e., DON3Glc, 3Ac-DON, 15Ac-DON) [29]. Authenticity and method performance have been demonstrated by analyzing naturally contaminated samples, such as malt, beer and maize [30].…”
Section: From Targeted Lc-ms/ms Determination To Untargeted Hr-ms mentioning
confidence: 99%
“…For the development of improved and accurate analytical methods and toxicological risk assessment, sufficient quantities of these compounds are required in high purity. Furthermore, isotope‐labeled conjugates are crucial for accurate quantification of mycotoxin metabolites by LC–MS , …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 13 C‐labeled DON‐3‐ O ‐β‐ d ‐[ 13 C 6 ]glucoside was accomplished by Königs–Knorr glycosylation (Ag 2 CO 3 in dichloromethane) by Habler et al very recently. However, the authors reported several drawbacks of their method: (i) an excess of isotope‐labeled glucosyl donor; (ii) a very long reaction time (5 d); and (iii) failed scale‐up of the reaction …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations